2018
DOI: 10.1063/1.5044519
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies on the elasticity of tungsten to 13 GPa

Abstract: Compressional (VP) and shear wave (VS) velocities of polycrystalline tungsten have been measured up to ∼13 GPa at room temperature using ultrasonic interferometry in a multi-anvil apparatus. Using finite strain equation of state approaches, the elastic bulk and shear moduli and their pressure dependences are derived yielding KS0=325.9±4.8  GPa,  G0=164.1±2.5  GPa, KS0′=3.65±0.05, and G0′=1.28±0.02. On the basis of the current experimental data, the high-pressure behavior of Young's modulus, Poisson's ratio, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…Using linear regression analysis approaches, the elastic moduli of the single-crystal tungsten were calculated. It was found that the Young's modulus, shear modulus, and bulk modulus, as well as Poisson's ratio, show a clear increasing trend with the increase in pressure, which is in good agreement with the experimental results [15]. In addition, the Pugh's modulus ratio of the single-crystal tungsten increases with the increase in pressure, implying that hydrostatic compression can effectively improve the ductility of BCC tungsten.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Using linear regression analysis approaches, the elastic moduli of the single-crystal tungsten were calculated. It was found that the Young's modulus, shear modulus, and bulk modulus, as well as Poisson's ratio, show a clear increasing trend with the increase in pressure, which is in good agreement with the experimental results [15]. In addition, the Pugh's modulus ratio of the single-crystal tungsten increases with the increase in pressure, implying that hydrostatic compression can effectively improve the ductility of BCC tungsten.…”
Section: Discussionsupporting
confidence: 86%
“…Figure 5c illustrates that the bulk modulus B varied in the range of 300-374 GPa, rising almost linearly with the increase in applied pressure. The predicted trends and values of Young's, shear, and bulk moduli agree well with the experimental work of Qi et al [15], who observed that the shear and bulk moduli of polycrystalline tungsten both increase monotonically with an increase in pressure. Obviously, the higher the external pressure, the closer the distance between atoms (see Figure 4) and the more densely compacted the lattice structure.…”
Section: Role Of Pressure In Elastic Propertiessupporting
confidence: 89%
See 3 more Smart Citations